LITERATURE REVIEW: PHARMACOLOGICAL AND TOXICOLOGICAL EFFECTS OF PLANTS FROM THE SOLANACEAE FAMILY - Damayanti Abdul Karim, Dewi; Safutri, Wina; Hammami, Akmal; Ayu Chandra, Ananda (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Solanaceae is a family of flowering plants with 83 genera and 2,925 species spread throughout the world. People reuse natural medicines that have been passed down from generation to generation because medical medicines have a big tendency to cause many side effects. This research aims to examine the pharmacological effects and toxicity of plants in the Solanaceae family. This research used 10 plant species, including potatoes (Solanum tuberosum L.), golden berries (Physalis angulata L.), tomatoes (Solanum lycopersicum L.), red chilies (Capsicum annuum L.), cayenne peppers (Capsicum frutescens L.), tobacco (Nicotiana tabacum L.), paprika (Capsicum annuum var. grossum), amethyst (Datura stramonium L.), Turkey berry (Solanum torvum Sw.), and black nightshades (Solanum nigrum L.). The journal search method used in this research is the Boolean System method (AND and OR) using the Google Scholar and Sinta databases. The results obtained from this research were that among the 10 plant species of the Solanaceae family studied, there were 3 pharmacological effects with the most data modes, including antimicrobial, anti-inflammatory, and anti-oxidant effects.